Pengaruh Pembelajaran Bahasa Arab Dengan Media Visual (Kartu Permainan) Menggunakan Teknik Think Pair Share Dalam Meningkatkan Minat Siswa Kelas VIII MTs Al-Kariim Sari Galuh Kampar - Reni Ulfita (CV. ULIL ALBAB CORP, 2024)
This research is an experimental study that the researcher conducted with the aim of finding out the effect of learning Arabic with Visual Media (Game Cards) using the Think Pair Share Technique to increase the interest of class VIII students at MTs AL-Kariim Sari Galuh Kampar. The formulation of the problem in this research is what and how the application of Arabic language learning with visual media (game cards) using the Think Pair Share technique can improve class VIII students at MTs Sari Galuh Kampar. The population in this study was all class VIII students at MTs AL-Kariim Sari Galuh Kampar. The samples used by researchers were students in classes VIII A and VIII B of MTs AL-Kariim Sari Galuh Kampar which were used as the experimental class and control class. Data collection is carried out by means of observation, tests and communication. Apart from that, the researcher used the t test and SPSS application to find out the results of the research. And it can be seen that there is a significant difference in the use of the Think Pair Share technique in the experimental and control classes tt 2.045 < 6.594 or 0.05 < 0.000, meaning that there is a significant difference between the interest of students who use the Think Pair Share technique (game cards) in improving Class VIII students at MTs AL-Kariim Sari Galuh Kampar with an increase of 5% and from 73%-81% with very good information. This means Ho is rejected and Ha is accepted